(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: This study aims to assess the efficacy and safety of implantable collamer lens (ICL) implantation in correcting moderate to high myopia, with a particular focus on its impact on anterior segment parameters, including anterior chamber depth (ACD), intraocular pressure (IOP), and endothelial cell density. Material and methods: A prospective, interventional observational study was conducted at a tertiary eye care center from August 2023 to May 2024. Twenty-six patients (44 eyes), aged 18 to 35 years, underwent ICL implantation. Preoperative and one-month postoperative measurements included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), spherical equivalent (SE), IOP, ACD, central corneal thickness (CCT), and endothelial cell counts. Data were analyzed using paired t-tests and ANOVA with IBM SPSS version 25. Results: The mean preoperative SE improved from −11.49 ± 4.78 D to −0.87 ± 0.40 D postoperatively (p < 0.001). UDVA improved significantly from 0.11 ± 0.035 to 0.87 ± 0.23 (p < 0.001), and CDVA improved from 0.85 ± 0.23 to 1.0 ± 0.18 (p < 0.001). No statistically significant change in IOP was observed (p = 0.2). ACD decreased significantly from 3.32 ± 0.24 mm to 2.59 ± 0.28 mm (p < 0.0001). Endothelial cell count showed a slight but non-significant decrease (p > 0.05). Conclusion: ICL implantation is a safe and effective option for correcting moderate to high myopia, with significant improvements in visual acuity and acceptable changes in anterior chamber parameters. Ongoing monitoring of anterior segment structures is recommended for long-term safety evaluation.